Footsoldiers political party membership in the 21st century - Bale, Tim 1965-; Webb, Paul; Poletti, Monica (Routledge, 2020)
"This accessible, rigorously researched and highly revealing book lifts the lid on political party membership. It represents the first in-depth study of the UK's six biggest parties - Labour, the Conservatives, the SNP, the Lib Dems, UKIP and the Greens - carried out simultaneously, thereby providing invaluable new insights into members' social characteristics, attitudes, activities and campaigning, reasons for joining and leaving, and views on how their parties should be run and who should represent them. In short, at a time of great pressure on, and change across parties, this book helps us discover not only what members want out of their parties but what parties want out of their members. This text is essential reading for those interested in political parties, party membership, elections and campaigning, representation, and political participation, be they scholars and students of British and comparative politics, politicians, journalists and party members - in short, anyone who cares about the future of representative democracy"--
Description based on online resource; title from digital title page (viewed on September 26, 2019)
Keywords: Party affiliation / Great Britain; Political parties / Great Britain